UPAYA MENINGKATKAN PEMBELAJARAN LOMPAT TINGGI MELALUI PENDEKATAN PERMAINAN LOMPAT PUNGGUNG PADA SISWA KELAS V SD NEGERI 06 PURWOHARJO KECAMATAN COMAL KABUPATEN PEMALANG TAHUN AJARAN 2012/2013 (Department of Physical Education, Sport, Health and Recreation, 2014)
This study aims to determine the high jump effort to improve learning through play approach to jump back in the fifth grade students SD Negeri 06 Purwoharjo Kecamatann Comal Pemalang Academic Year 2012/2013. This type of research PTK. Object of study is the fifth grade students SD Negeri 06 Purwoharjo Comal Pemalang District School Year 2012/2013, amounting to 35 students made ​​up of 20 boys and 15 female student. Physical education teacher and our partners in this role as an observer or observers during the learning takes place, while the researchers themselves implementing learning or as a teacher. This study sport is learning the high jump by jumping back approach. Data collection techniques used observation and tests. Analysis using quantitative descriptive. The results showed that students' learning activities fifth grade students of SD Negeri District 06 Purwoharjo Comal Pemalang Academic Year 2012/2013 show mastery learning on prasiklus 34.29%, 57.14% first cycle and the second cycle at 80%. Conclusion This study shows that exercise jump back effectively to improve learning outcomes Jump High in Class V SD Negeri District 06 Purwoharjo Comal Pemalang Academic Year 2012/2013.